Moral Panics - Thompson, Kenneth (Key Ideas, 1998)
It is widely acknowledged that this is the age of moral panics. From the Bulger case to mad cow disease, newspaper headlines continually warn of some new danger and television programmes echo the theme with sensational docmenturies.This concise survey will help student trace the development of ideas of moral panic and to analyse how changing public perceptions are shaped and reflected through the media over time. Using examples drawn from:* club culture and raves* mugging* sex and AIDS* children, violence and the family.